Utilization of Social Media in Teacher Interpersonal Communication with Students with Special Needs - Audina Putri; Aina Sabriyanti; Imam Hardani Ritonga; Putri Asa Parent; Kartini Kartini (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
The purposes ond conclution of this research are to find out how the application of interpersonal communication between teachers and deaf students extraordinary school in the utilization of social media, to find out what factors hinder and support the application of interpersonal communication in the utilization of social media extraordinary school, and to know what impact occurs on students in the utilization of social media in interpersonal communication with the teacher, which is the overall purpose of this research by paying attention to the quality of supportive attitudes. The method used in this research uses qualitative research methods with a case study research approach.The results of this research are when communicating, teachers and deaf students pay attention to the language used. Teachers and students alike try to be honest and try to position themselves as interlocutors when communicating. The inhibiting factor is the vocabulary of deaf students, studentsare not able to speak clearly, students who are initially dishonest and students who are not easily cured. While the supporting factors are students like to ask questions and tell the teacher, the teacher who always forgives students, honest students because the evidence that the teacher has and the teachers and students positioning themselves as interlocutors when communicating. The impact that occurs on students are increasing vocabulary of students, students who increasingly become honest and students who increasingly understand the teacher.